Protocol, rationale and design of DAbigatran for Stroke PreVention In Atrial Fibrillation in MoDerate or Severe Mitral Stenosis (DAVID-MS): a randomised, open-label study. Issue 9 (25th September 2020) - Zhou, Mi; Chan, Esther W; Hai, Jo Jo; Wong, Chun Ka; Lau, Yuk Ming; Huang, Duo; Lam, Cheung Chi; Tam, Chor Cheung Frankie; Wong, Yiu Tung Anthony; Yung, See Yue Arthur; Chan, Ki Wan Kelvin; Feng, Yingqing; et al.
Abstract : Introduction: Current international guidelines recommend non-vitamin K oral anticoagulants (NOACs) for stroke prevention among patients with non-valvular atrial fibrillation (AF) at significant ischaemic stroke risk given the superior safety and comparable efficacy of NOACs over warfarin. Nonetheless, the safety and effectiveness of NOACs have not been evaluated in patients with AF with underlying moderate or severe mitral stenosis (MS), hence the recommended stroke prevention strategy remains warfarin therapy. Method and analysis: MS remains disproportionately prevalent in Asian countries compared with the developed countries. This prospective, randomised, open-label trial with blinded endpoint adjudication aims to evaluate the safety and efficacy of dabigatran for stroke prevention in AF patients with moderate or severe MS. Patients with AF aged ≥18 years with moderate or severe MS not planned for valvular intervention in the coming 12 months will be randomised in a 1:1 ratio to receive dabigatran 110 mg or 150 mg two times per day or warfarin with international normalised ratio 2–3 in an open-label design. Patients with estimated creatinine clearance <30 mL/min, or with a concomitant indication for antiplatelet therapy will be excluded. The primary outcome is a composite of stroke and systemic embolism. Secondary outcomes are ischaemic stroke, systemic embolism, haemorrhagic stroke, intracranial haemorrhage, major bleeding and death. The estimated required sample size is approximately 686 participants. Ethics and dissemination: The study protocol has been approved by the Institutional Review Board of the University of Hong Kong and Hong Kong West Cluster, Hospital Authority, Hong Kong for Fung Yiu King Hospital, Grantham Hospital, Queen Mary Hospital and Tung Wah Hospital in Hong Kong. Results will be published in peer-reviewed journals. Trial registration number: ClinicalTrials.gov Registry (NCT04045093 ); pre-results.